Analysis of the Relationship Between Work Posture and Low Back Pain Complaints Among Dock Workers at Ferry Bolok Port - Emirensiana Wain; Noorce Ch. Berek; Mustakim Sahdan; Sintha Lisa Purimahua (Universitas Ibn Khaldun Bogor, 2026)
Low back pain is one of the most common complaints in various types of work, including among stevedores at Ferry Bolok port. This condition may occur when workers perform activities with non-ergonomick postures. This study aims the relationship between work posture and low back pain complaints among stevedores at Ferry Bolok port. This research used an anlytic survey with a cross-sectional design. The sampling technique was total sampling, involving 42 stevedores. Data were analyzed using univariate and bivariate analysis to describe the characteristics of each variable and to asses the relationship between the independent and dependent variables. The chi-square test was used to measure the relationship. The results showed that low back pain complaints were mostly experienced by respondents aged 50-60 years (59,5%), with a working period of ≥ 5 years (52,4%). In terms of lifting posture, 24 respondents (57,1%) had a lifting indeks (LI) > 1.0, and 6 respondents (14,3%) had an LI > 3.0. the study also revealed thet there was no significant relationship between pushing posture and low back pain complaints. It is recommended that stevedores pay more attention to their working posture, particularly in lifting activities, by maintaining a relaxed position and avoiding lifting loads that exceed their muscular capacity or that requaire moving objects over long distances.